Automated group decision support system - Pietukh, A. M.; Voitko, V. V.; Kuzmin, Ye. V.; Kuzmina, N. F. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The models of the system of group decision making support in the interactive environment of collective collaboration have been developed. The developed automated system provides the possibility of correct support of group decisions in the process of implementation of different working modes for user groups and ensures efficient solutions of conflict situations.